The Use of Beauty Products in Purchasing Decisions Reviewed from the Perspective of Product Quality and Brand Image - Tessa Handra; Subandriyo; Lod Sulivyo; Faye Maya Dewi (JOURNAL INTELEKTUAL, 2025)
Introduction/Objective: This study discusses the analysis of the Influence of Product Quality (X1) and Brand Image (X2) on Purchase Decisions (Y) of Beauty Products on Female Students in Private Institutions in Tangerang Regency.. Background of the Problem: The growth of the beauty industry in Indonesia has experienced rapid growth, beauty products have become primary needs and not just secondary needs and consider beauty products as self-expression and a means to increase self-confidence. Novelty: Analyzing the same variables according to previous research by testing different research locations and samples. Research Method: Using a quantitative descriptive approach, data was taken from users of local cosmetic brands obtained 71 samples with Slovin's theory and the tool for analysis used was SPSS. Findings/Results: It is proven that there is an influence that can positively consider purchasing decisions, namely product quality (X1) and brand image (X2) on local cosmetic users among female students. Conclusion: This finding provides important implications in paying attention to product quality and brand image in purchasing decisions in terms of cosmetic products because beauty products are their self-expression